PERLINDUNGAN HUKUM PIHAK PENJUAL DALAM AKTA JUAL BELI YANG DIBUAT PEJABAT PEMBUAT AKTA TANAH TERKAIT PENYALAHGUNAAN KEADAAN DAN AKIBAT HUKUMNYA - Idham Kholid; Felicitas Sri Marniati; Iran Sahrir (Bajang Institute, 2025)
Land sale and purchase agreements must be based on mutual agreement free from coercion, fraud, and error. Abuse of circumstances often occurs in land sale and purchase practices in Indonesia, even though the implementation is made by an authorized official, namely the Land Deed Official. The formulation of the research problem is regarding the legal consequences of sales and purchase deeds made by land deed officials related to abuse of circumstances and how the legal protection of the seller in sales and purchase deeds made by land deed officials related to abuse of circumstances. The theories used are the theory of legal consequences from R. Soeroso and legal protection from Satjipto Rahardjo. The method used in this research is normative juridical, this research uses secondary data with primary, secondary and tertiary sources. The research approach used is the legislative approach, case, analytical, conceptual, and legal material collection techniques are carried out by identifying and inventorying positive legal regulations, book literature, and other legal material sources. For legal material analysis techniques, legal interpretation techniques are carried out, namely grammatical interpretation and systematic interpretation as well as legal construction, namely analogy construction and legal refinement construction. The results of the reasearch can be concluded, the legal consequences of the sale and purchase deed made by land deed official related to the abuse of circumstances (misbruik van omstandigheden) is that the sale and purchase deed does not produce fully binding legal consequences, because there is a defect in the will of one of the parties and legal actions that do not meet subjective requirements such as free will resulting in imperfect legal consequences, namely the sale and purchase deed can be canceled through a court decision, with this cancellation the seller obtains legal protection. The government should provide further regulation regarding the provisions of Article 22 of Government Regulation Number 37 of 1998 concerning the Position of the Land Deed Official, particularly with regard to the declaration of the parties affirming that they are acting voluntarily and that no hidden legal arrangement exists behind the sale and purchase agreement which could lead to a defect of will in the execution of the deed.